EKSEKUSI RIEL PUTUSAN HAKIM TERHADAP BENDA TIDAK BERGERAK - Pradiptha Wirjana, I Putu Wahyu; Agung, I Gusti Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2013)
Decisions that legally enforceable could do the execution. One of the executionswas real execution. The object of Real Execution can be fixed or moving objects, andone of which is land. In practice, not kind of all execution can be carried out and thereare many constraints in such the party received an order from a decision that is notvoluntarily hand over the object to be executed so that the party filed a deferment ofexecution. Deferment of execution that underlies are the physical resistance thatendangers the safety of officers and the boundaries of the soil such as the river thatanytime are subject to change.
Keywords: Real execution, Execution conducted, Execution constraints.